AI in Human Extraterrestrial Settlement on Mars - Khade, Pranay; Rohit Kadam; Rajshree Patale; Sheetal Rajapurkar (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Human settlements on Earth have been successful due to two essential factors: human evolution and mutual support. However, in order to continue this trend in space-based settlements, advanced technology will be required. Settlements on Mars will need human-machine collaboration, where AI will augment human skills and knowledge. Current missions near Earth have been successful due to contingency planning by organizations like ISRO, NASA, Roscosmos, and ESA. However, when it comes to traveling to Mars, technology developers have limited knowledge of the environment in which AI needs to operate. Thus, new algorithms will need to be developed to work in partially observable environments. While humans can survive brief periods without power or water, handling infrastructure failures requires significant human involvement. Today, AI is being developed to help robots monitor critical infrastructure using machine learning algorithms. Both construction and protection of future space infrastructure will heavily rely on such evolving technologies. Additionally, AI will play a vital role in the mobility of future space settlements. AI will be built into robots to navigate partially known and unknown terrains. The approach used by most robots for navigation is called heuristic search, where a robot takes in a map with available data about a terrain and uses rules or heuristics to identify optimal paths. In summary, human settlements in space will rely on advanced technology, including AI, to augment human skills and knowledge. As the environment will be unfamiliar and partially observable, new algorithms will need to be developed. Such technologies will also help handle infrastructure failures and support mobility in the settlements, making them sustainable for future generations.